2015
DOI: 10.1093/eurpub/ckv034
|View full text |Cite
|
Sign up to set email alerts
|

Trends in adolescents' perceived parental communication across 32 countries in Europe and North America from 2002 to 2010

Abstract: The temporal trends demonstrated an increase in a positive health asset for many young people, that of family communication. Positive trends may be a feature of the economic boom over the past decade coupled with cultural changes in attitudes to parenting, especially fathering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 12 publications
1
37
0
1
Order By: Relevance
“…One study using data from the Health Behaviour in School‐aged Children distributed among 11–15‐year‐old adolescents in 32 countries revealed that communication with mothers and fathers increased in some countries between 2002 and 2010, whereas it decreased in others. In Sweden, maternal communication increased marginally, while paternal communication decreased slightly . However, given the weak positive trend for maternal communication and the reverse trend for paternal communication, we believe that it is unlikely that the doubling of non‐drinking ninth graders (15–16 years) that has occurred since 2000 in Sweden is due to changes in parent–child communication.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…One study using data from the Health Behaviour in School‐aged Children distributed among 11–15‐year‐old adolescents in 32 countries revealed that communication with mothers and fathers increased in some countries between 2002 and 2010, whereas it decreased in others. In Sweden, maternal communication increased marginally, while paternal communication decreased slightly . However, given the weak positive trend for maternal communication and the reverse trend for paternal communication, we believe that it is unlikely that the doubling of non‐drinking ninth graders (15–16 years) that has occurred since 2000 in Sweden is due to changes in parent–child communication.…”
Section: Introductionmentioning
confidence: 83%
“…The present study used data from the Swedish subsample of the European School Survey Project on Alcohol and Other Drugs (ESPAD), which is a survey that has been distributed since 1995 to monitor the use of alcohol and other substances in different European countries. The Swedish subsample is an anonymous pen and paper questionnaire that is completed in the classroom by ninth graders (15)(16) ESPAD is a collaboration between 48 European countries with data available from 25 countries for the period from 2003 to 2015. However, only data from Sweden were used, since we wanted to evaluate the role of parenting factors in a single country before testing whether these factors are associated with the international trend of non-drinking.…”
Section: Participantsmentioning
confidence: 99%
“…Recently a growing body of work has identified the importance of connections with parents during adolescence for the maintenance of emotional wellbeing and health during adolescence (Brooks et al 2015b; Cava et al 2014; Levin et al 2012; Rothon et al 2012). The finding of an association between self-harm and positive communication with parents is in line with previous research that indicates that young people who reported self-harm have fewer people they can talk to about their problems (Evans et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Given the large number of children living in stepfamilies, it is also important to understand how adolescents perceive communication with their non-biological parents over time. The current study builds upon recent research on factors that are associated with adolescents' communication in intact and stepfamilies (12,15,17) and extends the knowledge about changes in parent-adolescent communication at the beginning of the new millennium (14,34). It examines the secular trend in the perceived ease of parent-adolescent communication within a large and representative adolescent population.…”
Section: Research Aimmentioning
confidence: 95%